(untitled) (Baghdad Science Journal, 2005)
the results pointed out that the average of energy amount obtained by the pregnant women was less than RDA so it amounted to 2014.4 keal/day which caused the birth weight to decrease to 2.8 kg which is less than the normal weight of a new-born child.